NACIONALISMO Y EDUCACIÓN: LA REFORMA EDUCATIVA DEL 2006 EN MÉXICO Y SU NUEVA VERSIÓN DE LA INDEPENDENCIA EN LOS LIBROS DE TEXTO DE EDUCACIÓN SECUNDARIA - Peña Guzman, Celina (Historia Caribe, 2010)
El presente artículo analiza la relación entre el nacionalismo y la educación en los textos de historia a nivel secundaria. De 1993 a la fecha, la reforma educativa ha transformado la enseñanza de la historia. Los textos eliminaron narrativas clave de los eventos del pasado. El enfoque nacionalista en historia ha sido excluido en estos libros. Palabras clave Nacionalismo, libros de texto de historia de secundaria, enseñanza de la historia, reforma educativa en México NATIONALISM AND EDUCATION: THE 2006 EDUCATIONAL REFORM IN MEXICO AND ITS NEW VERSION OF THE INDEPENDENCE IN SECONDARY LEVEL TEXTBOOKS ABSTRACT This article revises the relation between nationalism and education in history textbooks at secondary level. From 1993 to our days, the educative reform has gradually transformed the teaching of history. Today, history textbooks, eliminated key narratives of heroic episodes. The nationalism focus in history has been taken away from these textbooks. Keywords Nationalism, history textbooks of secondary level, history teaching, educative reform in Mexico